Pengaruh Pemberian Ekstrak Teripang Pasir terhadap Hambatan Pertumbuhan Shigella Dysentriae Secara In Vitro - FERIZAL NEGERI SAMUDRA; RETNO BUDIARTI; Irmawati Dikman (Universitas Hang Tuah, 2020)
Abstract Background; In Indonesia, most diarrhea disease in 1995 to 2001 are caused by Shigella spp. Shigella spp infection can cause various symptom dan complication. Generally, the treatment by using antibiotic can cause antibiotic resistance. Sea cucumber (Holoturia scabra) is an herb that known, available, and easy to consume by society and has an antibacterial effect. Therefore, further research to study the effect of Holoturia Scabra on Shigella Dysentriae growth in vitro is needed. Objectives: The goal of this research is demonstrate the effect of sea cucumber (Holoturia scabra) to the growth of the Shigella dysentriae bacteria in vitro. Method: The method in this research is Posttest Only Control Group. There are 6 groups, 4 types of and 2 control groups. The concentration of the treatment group is 100%,50%, 25%, and, 12.5% while for positive control tests using chloramphenicol and aquadest as a negative control. Result: The result showed there is an influence on the intake of sand cucumber to the growth of the Shigella dysenteriae. Conclusion: Sea cucumber (Holoturia scabra) inhibit the growth of Shigella dysenteriae.